Association between gut microbiota and menstrual disorders: a two-sample Mendelian randomization study - Yao, Yufan; Hu, Haoran; Chen, Longhao; Zheng, Hong (Frontiers in Microbiology, 2024)
Background Evidence from observational studies and clinical trials suggests that the gut microbiota is associated with gynecological diseases. However, the causal relationship between gut microbiota and menstrual disorders remains to be determined.We obtained summary data of gut microbiota from the global consortium MiBio-Gen's GWAS dataset and data of menstrual disorders from IEU Open GWAS project. MR Egger, Weighted median, Inverse variance weighted, Simple mode, Weighted mode were used to examine the causal association between gut microbiota and menstrual disorders. Thorough sensitivity studies were performed to confirm the data' horizontal pleiotropy, heterogeneity, and robustness.Through MR analysis of 119 kinds of gut microbiota and 4 kinds of clinical phenotypes, it was discovered that 23 different kinds of gut microbiota were loosely connected to menstrual disorders. After FDR correction, the results showed that only Escherichia/Shigella (P=0.00032, PFDR=0.0382, OR=1.004, 95%CI=1.002-1.006) is related to menstrual disorders.Conclusions According to our MR Analysis, there are indications of a causal relationship between menstrual cycles. This finding could lead to new discoveries into the mechanisms behind menstrual disorders and clinical research involving the microbiota.